MAKING AND CHARACTERIZATION CELLULOSE THERMAL INSUALATION CORN HUSK BASED - Prasandhika - Nim: 13713027 , Akbar
The Building and Construction sector accounts for 30-40% world energy consumption, with a large part belonging to the need to heat and cool buildings. ThatÃ‚Â’s why improvisation of thermal insulation material in buildings are needed to provide the higher energy efficiency and also less energy consumption. Traditional insulation materials which were oftenly used are stone wool, fiber glass, polyurethane and polystyrene. While these materials are efficient in maintaining thermal comfort to building interior, they are made with nonrenewable resources and have a high embodied energy. Cellulose is renewable material which it have good thermal properties, acoustic properties, with the result that cellulose is good to become thermal insulation in building. Cellulose could be obtain from many agriculture waste, such as corn husk. It contains 31,339,3% cellulose. Because of the corn husk potential, the aims of the research is to make thermal insulation using corn husk which combined with epoxy. Density measurement and Chesson-Datta were done to characterization corn husk. Samples are made with various volume fraction of corn husk at 10%, 15%, 10%, 25% and mixed with epoxy. From the test result, corn husk has density 0,9333 gr/cm3, the content of cellulose is 24,5%, the optimum thermal is find in 20% volume fraction on corn husk i.e 0,933 W/mK, value of strength and stiffness of flexural, tensile are decrease in a row with increasing volume fraction of corn husk. The presence of voids or porosities cause low density, and the value of real volume fraction of sample is lower than specified value.